ФЕНОМЕНОТ НА НЕЧИСТОТО/ГРДОТО/ГРОЗНОТО ВО РОМАНОТ “ЦРНЕЦ” НА ТАТЈАНА ГРОМАЧА (Philological Studies, 2019)
Provocation is directed towards the duality, more specifically, towards the attraction and repulsion of the phenomenon of the impure/grotesque/disgusting in the novel Crnac by T. Gromaca (Durieux: Zagreb, 2004). Her story also affords the opportunity to be read from the aspect of a dark drama of purity (Koteska. Jasna. 2006. Sanitarna enigma. Templum, Skopje). In fact, the obsession for purity (as a dark enigma) very often goes hand in hand with the desire for order. In J. Krsteva’s essay, impurity is one of the four agents (together with taboo, food and sin) through which the category that she identifies as abject appears (Kristeva. Julija. 1982. Powers of Horror. An Essay on Abjection. Columbia University Press, New York). It is, in fact, the abject itself which most fundamentally undermines the stability of the subject. This is why society has a desperate need to hide, even to cover up, abject appearances. In that context, Gromaca also systematically describes her own depressing everyday life, as well as that of her family, in 138 very short chapters introduced as static fragments and separate images.